Calculation of the thermal units for 13 codes of the BBCH scale of 12 progenies of quinoa in the growing conditions of the Brazilian savanna (2021)
The introduction of quinoa (Chenopodium quinoa Willd.) in the Brazilian savanna has been successful based on the selection of progeny from valley types. Given the wide variation of environments, an alternative to define the maturation cycle of the plant has been the use of accumulated thermal units (ATU).  This measure allows prediction of the plant cycle and supports the definition of phenology duration useful in crop management and quinoa breeding. This study aimed at calculating the ATU for the 13 codes of the BBCH scale of quinoa by evaluating 12 selected progenies grown in two sowing dates, at 15° 56’ S and 47° 55’ W, altitude of 1.100 m, Brasilia, DF, Brazil. Statistical differences were predominant from the beginning of the BBCH-50 reproductive phases, classifying the progenies as early, mid-cycle and late. Early maturity progenies and respective ATU for BBCH-89 are BRQ4 (1.676,8), BRQ1 (1,685), and AUR (1,691), contrasting with late BLA (2.239), BRQ3 (1,929.1 GDD), and BRQ8 (1,895). The accumulated thermal units for BBCH-89 ranged from 1565.25 to 2381, with a difference between the earliest and latest genotypes of 815.75.  Progenies selected from existing cultivars are different in thermal unit accumulation, ensuing efficiency in cultivar acquisition to stagger quinoa cultivation. Accumulated thermal units explain the range of plant maturity cycles in selection. Additionally, the calculation of atu for BBCH scale codes is an effective tool for predicting the phenological cycle of quinoa.